Interactions between tenocytes and monosodium urate monohydrate crystals: implications for tendon involvement in gout. Issue 9 (7th April 2014) - Chhana, Ashika; Callon, Karen E; Dray, Michael; Pool, Bregina; Naot, Dorit; Gamble, Greg D; Coleman, Brendan; McCarthy, Geraldine; McQueen, Fiona M; Cornish, Jillian; Dalbeth, Nicola
Abstract : Objectives: Advanced imaging studies have demonstrated that urate deposition in periarticular structures, such as tendons, is common in gout. The aim of this study was to investigate the effects of monosodium urate monohydrate (MSU) crystals on tenocyte viability and function. Methods: The histological appearance of tendons in joints affected by advanced gout was examined using light microscopy. In vitro, colorimetric assays and flow cytometry were used to assess cell viability in primary rat and primary human tenocytes cultured with MSU crystals. Real-time PCR was used to determine changes in the relative mRNA expression levels of tendon-related genes, and Sirius red staining was used to measure changes in collagen deposition in primary rat tenocytes. Results: In joint samples from patients with gout, MSU crystals were identified within the tendon, adjacent to and invading into tendon, and at the enthesis. MSU crystals reduced tenocyte viability in a dose-dependent manner. MSU crystals decreased the mRNA expression of tendon collagens, matrix proteins and degradative enzymes and reduced collagen protein deposition by tenocytes. Conclusions: These data indicate that MSU crystals directly interact with tenocytes to reduce cell viability and function. These interactions may contribute to tendon damage in people with advanced gout.